Clinical and epidemiological profile of genotype 3 HCV patients in the South of Brazil - Costa, Marisa Boff; Longo, Larisse; Santos, Deivid; Costa, Raquel Boff da; Dellavia, Gustavo Hirata; Arruda, Soraia; Michalczuk, Matheus Truccolo; Álvares-da-Silva, Mário Reis (Clinical and Biomedical Research, 2020)
Introduction and aim. Despite the emergence of new treatments for genotype 3 HCV (G3 HCV), there is still a lack of data about this particular subgroup in Brazil. We aimed to describe clinical and sociodemographic variables and treatment profile of G3 HCV Brazilian patients. Methods. This was a descriptive, retrospective study, performed in a specialized center for HCV treatment in Brazilian South Region. Medical charts of patients diagnosed with G3 HCV were reviewed to collect clinical, sociodemographic and treatment information. Results. 564 subjects were enrolled, with mean age of 59.3 years (SD=10.5). Cirrhosis was present in 54.4% of patients. Most common co-existent conditions were systemic arterial hypertension (36.6%) and diabetes mellitus (30.0%). Regarding treatment, 25.2% of patients were treatment-naïve and 74.8% were currently treating (11.6%) or had received a previous treatment (87.0%). The most frequent ongoing treatment was sofosbuvir+daclatasvir(± ribavirin) (87.8%). Of the 388 patients who had at least one previous treatment, 67.0% achieved sustained virologic response in the last treatment. Caucasian/white, non-obese, transplanted patients, those with longer time since diagnosis and with cirrhosis were more likely to receive treatment, according to multivariate analysis. Patients with hepatocellular carcinoma had 64.1% less chance to be on treatment during the study period than those without this condition; patients with chronic kidney disease presents were 2.91-fold more likely to have a treatment interruption than those without. Conclusion. This study describes a large sample of Brazilian patients with G3 HCV. Treatment patterns were mainly influenced by presence of HCV complications and comorbidities.